Implications of Teacher Interpersonal Communication Ability on Student Learning Motivation in Islamic Religious Education Lessons During Pandemic - Amin, Alfauzan; Alimni, Alimni; Kurniawan, Dwi Agus; Triani, Elza; Pratama, Wahyu Adi (Journal of Education Reseach and Evaluation, 2022)
A During the pandemic, teachers' interpersonal communication skills are needed to create student learning motivation. One of the keys to the success of teaching teachers is the ability of teachers to build communication with students. So this research needs to be done with the aim of this research is to analyze the effect of interpersonal communication skills of teachers on students' motivation in learning Islam Religious Education during the pandemic. This type of research is Mix method research. The number of sample respondents is 72 students. Data collection techniques are using Random Sampling. In the hypothesis test, it was found that in the T test, it was found that there was a significant difference in the teacher’s Interpersonal Communication ability and students’ learning motivation in Islamic religious education subjects in each school and the results of the regression. The test showed that there was an influence between Teacher Interpersonal Communication on students’ learning motivation in the subjects of Islamic religious education lessons during the pandemic.